Application of Native Speaker Models for Identifying Deviations in Rhetorical Moves in Non-Native Speaker Manuscripts - Assef Khalili; Farahman Farrokhi; Majid Aslanabadi (Tabriz University of Medical Sciences, 2016)
Introduction: Explicit teaching of generic conventions of a text genre, usually extracted from native-speaker (NS) manuscripts, has long been emphasized in the teaching of Academic Writing inEnglish for Specific Purposes (henceforthESP) classes, both in theory and practice. While consciousness-raising about rhetorical structure can be instrumental to non-native speakers(NNS), it has to be admitted that most works done in the field of ESP have tended to focus almost exclusively on native-speaker (NS) productions, giving scant attention to non-native speaker (NNS) manuscripts. That is, having outlined established norms for good writing on the basis of NS productions, few have been inclined to provide a descriptive account of NNS attempts at trying to produce a research article (RA) in English. That is what we have tried to do in the present research. Methods: We randomly selected 20 RAs in dentistry and used two well-established models for results and discussion sections to try to describe the move structure of these articles and show the points of divergence from the established norms. Results: The results pointed to significant divergences that could seriously compromise the quality of an RA. Conclusion: It is believed that the insights gained on the deviations in NNS manuscripts could prove very useful in designing syllabi for ESP classes.